Pattern of Collection and Distribution of Zakat Fitrah 1444 H in ZISWAF Laboratory FEBI - Onti Laura Citra; Lanaa Fauziyyah; Pajar Wijaya; Andi Harpepen (Universitas Dehasen Bengkulu, 2023)
This journal is entitled